Teacher’s Strategies in Improving Students’ Reading Interest in Class III A Students at SD Negeri 105268 Telaga Sari, Kutalimbaru District, Academic Year 2022/2023 - Egi Verbina Ginting; Muhammad Fadly Syahputra; Putri Octavia Hafika; Romaito Abigail Sinaga; Zalma Putri Yani; Laurensia M. Perangin Angin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Increasing interest in reading must start with self-motivation in reading so that it can trigger the importance of reading for students and society. This study aims to determine the efforts made by the class teacher to increase the reading interest of class III A students at SD Negeri 105268. This research was conducted using the qualitative descriptive method. The results showed that the teacher had made several efforts to increase students' interest in reading, namely by retelling what students read, giving books according to their interests, giving gifts in the form of books, and doing literacy every hour of learning. So, it is necessary to carry out more varied activities to increase students' interest in reading by making in-depth observations about students' habits and something that attracts their attention.